MODEL-MODEL PENGEMBANGAN MEDIA DAN TEKNOLOGI PEMBELAJARAN - Sudianto; Muh. Khalifah Mustami; Muh. Yusuf T. (Pondok Pesantren Baitul Qur`an Sambas, 2024)
The actual phenomenon that occurs in the world of education today is that there are differences in perceptions regarding the term learning media. Learning media is a very important concept in the world of education. Even though learning media has an important role, currently differences in perceptions regarding learning media have become a crucial problem in the world of Indonesian education. These differences in perception have resulted in the emergence of erroneous understandings regarding learning media. One effort that can be made to avoid misconceptions about learning media is to deepen the concept of learning media among educational scientists. From the information presented in the discussion section, it can be concluded that a model is a series of activities or activities in which there are work procedures, rules and systematic thought patterns to produce or achieve maximum goals. Meanwhile, development is defined as a concept in the process of creating and managing all media and technology in order to maximize the learning process. The media and learning technology development models that can be used are the ASSURE Model, PIE Model, Roblyer Model, and Hannafiin and Peck Model.